2022
DOI: 10.30650/ajte.v4i1.3200
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Research Dilemmas and Their Implications In English Language Teaching Studies

Abstract: Researchers across the disciplines, including those whose passions are in English teaching studies, are always challenged to continuously contribute their research findings to the development of science. However, ethical considerations must be adhered to when they involve humans as participants in their study. Ethical dilemmas, even though they are considered important, are still rarely discussed. Thus, depicting the sketch of a comprehensive configuration of ethical dimensions is extremely needed for ESL rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(46 reference statements)
0
1
0
1
Order By: Relevance
“…The current study was conducted at a school in Semarang, under the guidance of the school's head coordinator. Prior to the commencement of the research, informed consent was obtained from the school administration, parents or guardians of the participating students, and the students themselves (Ginting, 2022). Through a brief interview with the coordinator, it was revealed that the English language skills and reading comprehension of elementary students in the 5th and 6th grades were found to be lacking and required improvement.…”
Section: Methodsmentioning
confidence: 99%
“…The current study was conducted at a school in Semarang, under the guidance of the school's head coordinator. Prior to the commencement of the research, informed consent was obtained from the school administration, parents or guardians of the participating students, and the students themselves (Ginting, 2022). Through a brief interview with the coordinator, it was revealed that the English language skills and reading comprehension of elementary students in the 5th and 6th grades were found to be lacking and required improvement.…”
Section: Methodsmentioning
confidence: 99%
“…Respondents to surveys filled out the questionnaires. "Questionnaire" is "a set of printed or written questions with a choice of responses, created for the purpose of a survey or statistical study" (Ginting, 2022), For this study, a questionnaire was created by the researchers themselves. Study relied on 5-point Likert scale to collect data.…”
Section: Methodsmentioning
confidence: 99%
“…Peneliti memperhatikan prosedur informed consent pada penelitian ini (Ginting, 2022) yaitu memperoleh izin dari kepala sekolah untuk melangsungkan penelitian. Untuk menjamin kerahasian, peneliti menjaga identitas sekolah dan peserta didik dalam penelitian ini.…”
Section: Metode Penelitianunclassified